Vulnerability factors associated with HIV/AIDS hospitalizations: a case-control study - Livia Maria Lopes; Rubia Laine de Paula Andrade; Tiemi Arakawa; Gabriela Tavares Magnabosco; Maria Ines Battistella Nemes; Antonio Ruffino Netto; Aline Aparecida Monroe
ABSTRACT Objectives: to identify the association between HIV/AIDS hospitalizations and factors that integrate individual, social, and programmatic vulnerabilities. Methods: a case-control study conducted in 2014 in a municipality in the state of São Paulo. "Cases" included people living with HIV (PLHIV) hospitalized and "control" those who were outpatients. Interviews were conducted using a tool with sociodemographic variables, clinical characteristics and other vulnerabilities. Data were analyzed by conditional logistic regression. Results: fifty-six cases and 112 control participated. Risk factors for HIV hospitalization were: unemployed and retired individuals; homeless people; non-antiretroviral users; individuals who did not regularly attend returns. Access to social workers was a protective factor for hospitalization. Conclusions: this research contributed to measure the social, individual and programmatic vulnerabilities that interfere with HIV worsening and, consequently, unfavorable outcome such as hospitalization.